2009
DOI: 10.1525/cond.2009.090058
|View full text |Cite
|
Sign up to set email alerts
|

Epaulet Color and Sexual Selection in the Red-Winged Blackbird: A Field Experiment

Abstract: Resumen. La mancha alar en los machos de Agelaius phoeniceus funciona tanto en el contexto intra-sexual como inter-sexual, pero existe poca evidencia de que ésta covaríe con el éxito reproductivo en esta especie, que ha sido bastante estudiada. Utilizamos un análisis de pasos usando caracteres territoriales de los machos, éxito de apareamiento y éxito reproductivo de los machos no manipulados para estimar la selección direccional actual. El tamaño de los territorios tuvo un efecto positivo sobre el número de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…As a result, if eavesdroppers in closed habitats rely more on acoustic signalling than vision compared to open habitats, we might expect birds in forests to evolve higher frequency songs within narrower bandwidths to avoid detection by unintended receivers such as predators or brood parasites (Hale, ; Lima, ). While the AAH assumes that bird song is selected for maximum distance propagation, the cost of eavesdropping by predators and parasites might counteract the benefit of auditory signals reaching additional potential mates or rival conspecifics (Mougeot & Bretagnolle, ; Yasukawa et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, if eavesdroppers in closed habitats rely more on acoustic signalling than vision compared to open habitats, we might expect birds in forests to evolve higher frequency songs within narrower bandwidths to avoid detection by unintended receivers such as predators or brood parasites (Hale, ; Lima, ). While the AAH assumes that bird song is selected for maximum distance propagation, the cost of eavesdropping by predators and parasites might counteract the benefit of auditory signals reaching additional potential mates or rival conspecifics (Mougeot & Bretagnolle, ; Yasukawa et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…I used presentations of taxidermic models of female Red‐winged Blackbirds in copulation‐solicitation postures to observe the behavior of males in five categories: (1) ASY floaters, (2) second‐year (SY) floaters, (3) experienced territorial males, (4) inexperienced territorial males, and (5) immediate territorial neighbors through the breeding season. I used this information to determine if (1) copulation behavior and success differed among floaters, territorial males, and territorial neighbors, (2) copulation behavior changed during the breeding season, and (3) copulation success rates of floaters, territorial males, and neighbors were consistent with fertilization success rates previously estimated by molecular paternity assignments for this study population (Yasukawa et al ).…”
mentioning
confidence: 70%
“…Of 77 successful copulations, 57 (74.0%) were by territory owners, 7 (9.1%) by neighbors, and 13 (16.9%) by floaters. DNA fingerprinting results from 1992 to 1994 (Yasukawa et al ) used to calculate expected frequencies (owners = 0.67, neighbors = 0.22, and floaters = 0.11) revealed that territory owners and floaters were overrepresented and neighbors underrepresented (χ 2 2 = 8.8, P = 0.012; Fig. B) in the number of successful copulations, assuming that all unassigned nestlings were sired by floaters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA from samples collected before 2000 were extracted using the methods reported in their respective studies ( Table 1; Yasukawa et al, 2009). DNA from samples collected after 2000 was extracted with a Qiagen DNeasy Blood and Tissue Kit (Hilden, Germany) and evaluated for concentration and purity using a Nanodrop spectrophotometer.…”
Section: Dna Extraction and Amplificationmentioning
confidence: 99%